White matter changes in fetal brains with ventriculomegaly - Horgos, Bianca; Mecea, Miruna; Boer, Armand; Buruiana, Andrei; Ciortea, Razvan; Mihu, Carmen-Mihaela; Florian, Ioan Stefan; Florian, Alexandru Ioan; Stamatian, Florin; Szabo, Bianca; Albu, Camelia; Susman, Sergiu; et al. (Frontiers in Neuroanatomy, 2023)
Introduction Ventriculomegaly (VM) is a fetal brain malformation which may present independently (isolated form) or in association with different cerebral malformations, genetic syndromes or other pathologies (non-isolated form). Methods This paper aims to study the effect of ventriculomegaly on the internal tridimensional architecture of fetal brains by way of Klingler's dissection. Ventriculomegaly was diagnosed using fetal ultrasonography during pregnancy and subsequently confirmed by necropsy. Taking into consideration the diameter of the lateral ventricle (measured at the level of the atrium), the brains were divided into two groups: moderate ventriculomegaly (with atrial diameter between 13 and 15 mm) and severe ventriculomegaly (with atrial diameter above 15 mm). Results and discussion The results of each dissection were described and illustrated, then compared with age-matched reference brains. In the pathological brains, fascicles in direct contact with the enlarged ventricles were found to be thinner and displaced inferiorly, the opening of the uncinate fasciculus was wider, the fornix was no longer in contact with the corpus callosum and the convexity of the corpus callosum was inverted. We have studied the prevalence of neurodevelopmental delay in children born with ventriculomegaly in the literature and discovered that a normal developmental outcome was found in over 90% of the mild VM cases, approximately 75% of the moderate and 60% in severe VM, with the correlated neurological impairments ranging from attention deficits to psychiatric disorders.